Defining catastrophic brain injury in children leading to coma and disorders of consciousness and the scope of the problem. Issue 6 (December 2020) - LaRovere, Kerri L.; Tasker, Robert C.
Abstract : Purpose of review: Severe brain injury in children resulting in coma and disorders of consciousness (DOC) is a catastrophic event for the life and function of children and their families. The present article summarizes the recently published pediatric literature on validated diagnostic assessments, potential predictors of recovery, and outcome measures used in children with catastrophic brain injury (CBI). Literature search terms included variants of consciousness, diagnostic tests, predictors of outcome, and outcome measures. Recent findings: Developmentally appropriate diagnostic tools, outcome predictors, and outcome measures are lacking for children with CBI leading to coma and DOC. Individual case prognosis relies on serial clinical examinations and experience. Evidence regarding optimal diagnosis of the highest level of consciousness and management of children with CBI is needed. Global efforts through the ongoing Curing Coma Campaign are aimed at: developing common data elements for information capture; streamlining the classification of coma endotypes; describing trajectories with biomarkers to monitor recovery or disease progression; and devising effective treatments for adults and children. Summary: Standardized, developmentally appropriate diagnostic and outcome assessments for CBI in children are needed. Future research should use these content standards to update our understanding of children with CBI leading to coma and DOC, and evaluate effective practices using acute adjunctive and rehabilitation therapies.